2019
DOI: 10.1007/s12671-019-01200-z
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Shared Flow and Perceived Emotional Synchrony on Compassion for Others in a Mindful-Dancing Program

Abstract: Objectives While there is a growing understanding of the relationship between mindfulness and compassion, this largely relates to the form of mindfulness employed in first-generation mindfulness-based interventions such as Mindfulness-Based Stress Reduction. Consequently, there is limited knowledge of the relationship between mindfulness and compassion in respect of the type of mindfulness employed in second-generation mindfulness-based interventions (SG-MBIs), including those that employ the principle of work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 61 publications
0
16
0
1
Order By: Relevance
“…Confirming the conceptual link between the constructs, communitas was strongly associated with both perceived emotional synchrony and identity fusion, while still distinct enough to establish discriminant validity and thus demonstrate the new measure's additional value according to the Fornell and Larcker (1981) criterion. Perceived emotional synchrony (also known as 'collective effervescence') experienced during collective events such as folkloric festivals, protest demonstrations, mindful dancing, and sport activities, has been shown to enhance collective identity, social cohesion, personal and collective self-esteem and efficacy, positive affect, positive social beliefs, compassion, and individual wellbeing ( Páez et al, 2015 ; Pizarro et al, 2020 ; Wlodarczyk et al, 2020 ). In a similar vein, the present study provides novel evidence of enduring prosocial and psychological benefits derived from the experience of communitas during a collective psychedelic experience.…”
Section: Discussionmentioning
confidence: 99%
“…Confirming the conceptual link between the constructs, communitas was strongly associated with both perceived emotional synchrony and identity fusion, while still distinct enough to establish discriminant validity and thus demonstrate the new measure's additional value according to the Fornell and Larcker (1981) criterion. Perceived emotional synchrony (also known as 'collective effervescence') experienced during collective events such as folkloric festivals, protest demonstrations, mindful dancing, and sport activities, has been shown to enhance collective identity, social cohesion, personal and collective self-esteem and efficacy, positive affect, positive social beliefs, compassion, and individual wellbeing ( Páez et al, 2015 ; Pizarro et al, 2020 ; Wlodarczyk et al, 2020 ). In a similar vein, the present study provides novel evidence of enduring prosocial and psychological benefits derived from the experience of communitas during a collective psychedelic experience.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is consistent with a previous and continuous line of research about participation and the role of PES (collective effervescence measure) as a predictor or mediator of the positive causal effects of participation in rituals and collective gatherings (derived from the theoretical tradition of Durkheim, 1912Durkheim, /2008Collins, 2004). It must be noted that previous longitudinal studies (pretest-during-posttest) have shown that PES predicts the positive effects of participation (e.g., von Scheve et al, 2017;Bouchat et al, 2020;Pizarro et al, 2020;Wlodarczyk et al, 2020;Zabala et al, 2020).…”
Section: Participation In Demonstrations As Social Belonging and Wellmentioning
confidence: 94%
“…A further study showed that brief mindfulness techniques used in an SG-MBI led to significant reductions in pain symptomatology and psychological distress in chronic pain patients (Cayoun et al 2019). Another study demonstrated the benefits of participating in an SG-MBI mindful-dancing program, in which the intervention's effects on compassion were found to be fully mediated by shared flow and perceived emotional synchrony (Pizarro et al 2019).…”
Section: Second-generation Mindfulness-based Interventionsmentioning
confidence: 97%